Reinventing government and bureaucracy in the Philippines old themes and a new image? - Reyes, Danilo R. (1994)
The author reviews Osborne's and Gaebler's propositions to reinvent government, and using the propositions, proceeds to analyze the bureaucratic reform agenda of the Philippine government. There are remarkable parallelisms between the reform goals of the western and Philippine blueprints. But where the western propositions are quite specific in identifying problems and solutions, the Philippine program of bureaucratic reforms appears as a "crowded shopping list of aspirations." Reinventing the Philippine bureaucracy to meet the demands of the Medium Term Philippine Development Plan for 1993-1998 requires, according to Reyes, fulfilling certain requisites related to: political will, the justice system, the implementation process, and reform priorities.
Keywords: Bureaucracy; Bureaucratization